Effect of Technology Introduction on Opak Productivity in Kebumen Village, Tersono District, Batang Regency - Najib, Ahmad; Arafat, Septrial; Kafabih, An’im (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
Opak production in Kebumen Village faces considerable challenges as it still uses traditional methods, resulting in low productivity and competitiveness in the market. The methods used were counseling, community empowerment, and introducing appropriate technologies such as drying ovens, cassava grinders, and oak dough molders to improve production efficiency. The program included training on Standard Operating Procedures (SOPs) and Occupational Safety and Health (OHS), as well as intensive mentoring for Micro, Small and Medium Enterprises (MSMEs) for 48 days. The implementation resulted in a 30% increase in production efficiency and a 20% decrease in work accidents. Applying this technology accelerates the production process, ensures product quality, and encourages innovation in digital marketing. The success of this program shows that the introduction of appropriate technology significantly contributes to improving the productivity, sustainability, and competitiveness of traditional food MSMEs. This empowerment model can inspire similar traditional food sector development in other areas with similar potential.